2020
DOI: 10.3389/fnagi.2019.00374
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Impact of Apolipoprotein E Epsilon 2 on Cognition and Brain Function in Cognitively Normal Elders and Mild Cognitive Impairment Patients

Abstract: Variants in the apolipoprotein E (APOE) gene play an important role in the development of Alzheimer's disease (AD). Specifically, the APOE ε4 allele is an established genetic risk factor for AD, while the APOE ε2 allele is a protective factor against AD. However, the mechanism underlying this impact of APOE genotype on the pathogenesis of AD remain unclear. This study sought to investigate the influence of APOE genotype on cognition and neuroimaging features in cognitively normal (CN) elderly individuals and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Notably, Conejero-Goldberg et al (2014) found that in ADNI data that MCI e4 carriers had a greater progression rate to AD, compared with e2 (HR for e4 vs. e2 was 3.95). E2 may interact with the neurodegeneration process to impact cognition, as a study by Gong et al (2019) found that the hippocampal volume and thalamus function mediated e2-associated cognitive performance in MCI, but not healthy older adults. These findings suggest that disease states could modify the APOE-cognition interaction, but more studies are warranted on this topic.…”
Section: Cognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, Conejero-Goldberg et al (2014) found that in ADNI data that MCI e4 carriers had a greater progression rate to AD, compared with e2 (HR for e4 vs. e2 was 3.95). E2 may interact with the neurodegeneration process to impact cognition, as a study by Gong et al (2019) found that the hippocampal volume and thalamus function mediated e2-associated cognitive performance in MCI, but not healthy older adults. These findings suggest that disease states could modify the APOE-cognition interaction, but more studies are warranted on this topic.…”
Section: Cognitionmentioning
confidence: 99%
“…Hippocampal volumetry is a well-established marker of neurodegeneration in AD. Studies in young and middle-aged and older adults have generally shown a tendency for larger hippocampal volume in e2 carriers ( den Heijer et al, 2002 ; Fennema-Notestine et al, 2011 ; Hostage et al, 2013 ; Khan et al, 2017 ; Gong et al, 2019 ). Findings in older adults are mixed and inconsistent.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…All the analyses were done in TBI group subjects and military control subjects respectively, and the interaction effect of TBI status was explored. Furthermore, as increased PVS may indicate the glymphatic system impairment, which would slow the clearance of brain waste like tau and Aβ and finally cause the occurrence of cognitive impairment, mediation analyses were done to investigate whether CSF biomarkers mediated the association between PVS and cognitive impairment using the SPSS PROCESS module ( 31 , 32 ). As there were four cognitive scales analyzed in this study, Bonferroni corrected p -value was set for 0.05/4 = 0.0125 for the analyses of cognitive scale.…”
Section: Methodsmentioning
confidence: 99%
“…All the analyses were done in TBI group subjects and military control subjects respectively, and the interaction effect of TBI status was explored. Furthermore, as increased PVS may indicate the glymphatic system impairment, which would slow the clearance of brain waste like tau and Aβ and finally cause the occurrence of cognitive impairment, mediation analyses were done to investigate whether CSF biomarkers mediated the association between PVS and cognitive impairment using the SPSS PROCESS module (31,32). As there were four cognitive scales analyzed in this study, Bonferroni corrected p-value was set for 0.05/4 = 0.0125 for the analyses of 1).…”
Section: Statistical Analysesmentioning
confidence: 99%